UNGKAPAN KEMPONAN DAN MAKNA SIMBOLIS TENTANG MAKANAN PADA MASYARAKAT KALIMANTAN BARAT (KEMPONAN EXPRESSION AND MEANING OF SYMBOLS ON THE FOOD OF THE PEOPLES OF WEST KALIMANTAN) - NFN Nindwihapsari (Kadera Bahasa, 2016)
In anthropology, food is considered as cultural phenomenon that bears meaning and has four symbolic function, such as social, group solidarity, food and soul tense, and symbolism of food in language. To enhance symbolic meaning of food, these functions were sometimes linked to beliefs and superstitions supported by sanction, that is superstitious and concrete punishment. The sanction took its form in kemponan expression. Kemponan is the belief of the society of West Kalimantan that emerge in the context of ignoring food and beverages offer to someone. In the culture of offering food and beverages, it is believed that person a who did not touch one serving that was offered, will meet disaster. This writting slightly discussed about kemponan expression in cultural perspective. The methods used is qualitative descriptive.  Source of the data is oral and written one. Source of oral data gained by observation, while written one gathered by scripts of folk tales that has been published. The technique of data collecting of the oral and written data are interview and taking notes. Finally, the writting is narrowed down to an insight that an expression, despite assumed as a media to express sense and sensibility, may show cultural events in each region, like kemponan expression that took root in oral tradition of West Kalimantan society.